PENGARUH MUSIK INDONESIA POP DAN KOREA POP TERHADAP TINGKAT KECEMASAN REMAJA PADA PEMERIKSAAN GIGI DI SMP NEGERI 9 KOTA TASIKMALAYA - Satriaanti Mulya, Trikanti; Samjaji; Rahayu, Culia (Jurnal Ilmiah Keperawatan Gigi, 2024)
Background: Dental anxiety is known to be a significant problem and an obstacle to the dental care process. Music can be applied as an effort to reduce anxiety, by providing music it can provide relaxation to reduce psychological anxiety. Purpose of this research is to determine the influence of Indonesian pop and Korean pop music on the level of anxiety of teenagers during dental examinations at SMP Negeri 9 Tasikmalaya City. Method: the research methods used was quasi experimental research with two group pre-post test design, the researcher divided the respondents into two groups, namely the group that was given Indonesian pop music as the first treatment group and the group that was given Korean pop music as the second treatment group. The examination is carried out using the Modified Dental Anxiety Scale (MDAS) and observing the pulse before and after the dental examination. Data analysis used the Wilcoxon test. Result: the result of the study showed that the significance value of the anxiety questionnaire with Indonesian pop music was 0,006, the significance value of pulse observation with Indonesian pop music was 0,008, the significance value of the anxiety questionnaire with Korean pop music was 0,016 and the significance value of pulse observation with Korean pop music was 0,001. Conclusion: there are influence from Indonesian pop and Korean pop music on teenagers anxiety level during dental examinations at SMP Negeri 9 Tasikmalaya City